Air–soil exchange of and risks posed by short- and medium-chain chlorinated paraffins: Case study in a contaminated area in China. (June 2022) - Ai, Qiaofeng; Zhang, Peixuan; Gao, Lirong; Zhou, Xin; Liu, Yang; Huang, Di; Qiao, Lin; Weng, Jiyuan; Zheng, Minghui
Abstract: Short-chain (SC) and medium-chain (MC) chlorinated paraffins (CPs) are found widely in the environment. Little research into air–soil exchange of SCCPs and MCCPs has been performed. In this study, CP concentrations, congener group profiles, and air–soil exchange in a typical contaminated area were investigated. A total of 10 soil samples and 10 air samples were collected from Zhoushan, an island in China. The samples were analyzed by two-dimensional gas chromatography electron capture negative ionization mass spectrometry. The SCCP and MCCP concentrations in the soil samples were 72–3842 and 117–8819 ng/g, respectively, and the SCCP and MCCP concentrations in the air samples were 57–208 and 1.8–25 ng/m 3, respectively. The highest CP concentrations in both soil and air were found in samples from near shipyards, possibly because of CPs being emitted from metal cutting fluids and marine paints used at the shipyards. C14 –15 Cl7-9 were the dominant CP congener groups in the soil samples. C10 Cl6–7 were the dominant CP congener groups in the air samples. Chlorinated decane and undecane and penta-, hexa-, and hepta-chlorinated CPs were enriched in the air relative to the soil. These congeners may have been released from the commercial CP-42 and CP-52. The fugacity fractions ( ff s) of 48 homologs decreased as Koa increased. The ff s indicated that SCCPs and MCCPs dominated deposition. The net air–soil exchange fluxes of CPs were 201–769 ng/(m 2 ·h). A preliminary risk assessment indicated that CPs pose low ecological risk except at sampling site S7 and do not pose significant health risks. Graphical abstract: Image 1 Highlights: High chlorinated paraffin (CP) concentrations were found in soil near a shipyard. Different CP congener group profiles were found for air and soil. Air–soil exchange of short- and medium-chain CPs was evaluated. Soil–air emission fluxes were markedly higher for short-than medium-chain CPs.